Rangka Manusia Berautomasi - Abd Jalil, Mohd Fazli Izwan (Universiti Sains Malaysia, 2006)
This project involves the application of using PIC16F877 microcontroller to control nine human skeletons. These skeletons were sent by National Museum of Malaysia. The main purpose of this project is to exhibit these automated skeletons at National Museum of Malaysia. All of these skeletons are known as Paleolitic age of skeletons named Perakman. Hardware and software were developed in this project where some instructions or programs were being uploaded to the microcontroller PIC16F877 to control motors, relays and other devices. All of these hardware were being installed inside the body of the skeletons to make them moving based on Perakman’s differents movements or movements depending on their characters. The programs were using PIC BASIC PRO language and Code Designer Lite as the editor. The compiler is PIC BASIC PRO Compiler and EPIC Programmer was used to upload the program into the microcontroller. PIC16F877 microcontroller was used to control dc motors and solenoids by using relays as a switch to the motors and solenoids to move the skeletons. Microcontroller PIC16F877 is also used to control Light Emitter Diode (LED). The durability and the reliability of the system is critical in this project as the Perakman’s exhibition was held for one month. The exhibiton was succesfully exhibited for one month.